Relationship between the development of lung squamous cell and grandular carcinoma recurrencesand the character of dysregeneratory changes in bronchial epithelium near the tumor - O. V. Pankova; V. M. Perelmuter; E. V. Denisov; S. A. Tuzikov; S. V. Miller; S. A. Vasilyev; N. A. Skryabin (Сибирский онкологический журнал)
Comparative analysis of the relationship between the character of dysregeneratory changes occurring in the bronchial epithelium adjacent to the tumor and the development of recurrence of squamous cell and grandular carcinomas of the lung was carried out. The study showed no any relationship between such parameters as tumor size, presence of lymphogenic metastasis, tumor stage and tumor recurrences. The incidence of recurrence in non-small cell lung cancer indirectly related to the character of dysregeneratory changes in the respiratory epithelium of the bronchial mucosa outside the tumor. High incidence rates of squamous cell carcinoma and adenocarcinoma of the lung were observed in cases with combination of basal cell hyperplasia and squamous metaplasia (BCH+SM+).